ANALISIS KINERJA BIDANG DIKMEN PADA DINAS PENDIDIKAN DAN KEBUDAYAAN DAERAH PROVINSI SULAWESI TENGAH - Miranda, Valdy (Katalogis, 2018)
This Study Aims To Determine Dikmen's Performance On Departement Of Education And Culture Central Sulawesi Province. The research method is descriptive qualitative to obtain in-depth information from informants. Determination of informants using purposive sampling as many as 7 people, namely the Head of Secondary Education, Section Head Coaching School, 1 staff Section Coaching School, Section Head of Vocational Guidance, 1 staff Section of Vocational Guidance, Section Chief P2PTK Dikmen and curriculum, and 1 staff section P2PTK Dikmen and Curriculum. The theory used is the theory Dwiyanto (2002: 48-49). Observation and study documents are also conducted to obtain data necessary. The results showed that the performance Dikmen Affairs at the Department of Education and Culture of the Provincial Central Sulwaesi not maximized. This is evident from the results of research based and proven to five aspects of the benchmark study focused only two studies that met and that indicator Responsibility and Accountability. While the Productivity Indicators, yet said to be optimal due to the lack of technical and human resources personnel participation is still lacking. While the Service Quality Indicators said is not optimal due to the lack of facilities and infrastructure to support service activities. Similarly Indicators Responsiveness can also be said not optimal because of the facilities and infrastructure was also back a bottleneck in responding to public education.